High mobility group box 1 as a biomarker in critically ill patients. Issue 8 (3rd June 2018) - Yagmur, Eray; Buendgens, Lukas; Herbers, Ulf; Beeretz, Anne; Weiskirchen, Ralf; Koek, Ger H.; Trautwein, Christian; Tacke, Frank; Koch, Alexander
Abstract : Background: Extracellular release of high mobility group box 1 (HMGB1) acts as a danger‐associated molecular pattern, thereby "alarming" the immune system and promoting systemic inflammation. We investigated plasma HMGB1 concentrations as a potential diagnostic and prognostic biomarker in critical illness. Methods: Our study included 218 critically ill patients (145 with sepsis, 73 without sepsis), of whom blood samples were obtained at the time‐point of admission to the medical intensive care unit (ICU). Results: High mobility group box 1 levels were significantly elevated in critically ill patients (n = 218) compared with healthy controls (n = 66). Elevated HMGB1 plasma levels were independent from the presence of sepsis. Moreover, HMGB1 was not associated with disease severity, organ failure, or mortality in the ICU. We observed a trend toward lower HMGB1 levels in ICU patients with pre‐existing obesity, type 2 diabetes and end‐stage renal disease patients on chronic hemodialysis. Conclusion: In conclusion, our study did not reveal significant associations between HMGB1 levels at ICU admission and clinical outcomes in critically ill patients. Due to the pathogenic role of HMGB1 in the late phases of experimental sepsis, future studies might assess the potential value of HMGB1 by measuring its plasma concentrations at later time points during the course of critical illness.